2002
DOI: 10.1016/s0096-3003(01)00072-8
|View full text |Cite
|
Sign up to set email alerts
|

q-Coherent pairs and q-orthogonal polynomials

Abstract: In this paper we introduce the concept of q coherent pair of linear functionals. We prove that if ðu 0 ; u 1 Þ is a q coherent pair of linear functionals, then at least one of them has to be a q classical linear functional. Moreover, we present the classification of all q coherent pairs of positive definite linear functionals when u 0 or u 1 is either the little q Jacobi linear functional or the little q Laguerre/Wall linear functional. Finally, by using limit processes, we recover the classification of cohere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…This is a generalization of the results obtained by I. Area, et al, in [3,5] for (1, 0)-q-coherent pairs. They showed that if (U, V) is a (1, 0)-q-coherent pair of quasi-definite linear functionals then at least one of them must be q-classical and one is a rational modification of the other as above with deg(σ(x)) ≤ 2.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…This is a generalization of the results obtained by I. Area, et al, in [3,5] for (1, 0)-q-coherent pairs. They showed that if (U, V) is a (1, 0)-q-coherent pair of quasi-definite linear functionals then at least one of them must be q-classical and one is a rational modification of the other as above with deg(σ(x)) ≤ 2.…”
Section: Introductionsupporting
confidence: 86%
“…Conversely, if there are constants a n = 0 and c n (λ, ω), 1 ≤ n ≤ M , such that (3.3) holds, then there exist constants b n with 5) such that (3.1) holds, i.e., (U, V) is a (1, 1)-D ω -coherent pair.…”
Section: )mentioning
confidence: 99%
“…This is a generalization of the results obtained by I. Area, E. Godoy, and F. Marcellán ([2,4] for ν = ω, [3] for ν = q) for (1, 0)-D ν -coherent pairs. They proved that (1, 0)-D ν -coherence is a sufficient condition for at least one of the linear functionals to be D ν -classical and each of them to be a rational modification of the other as above with deg(σ(x)) ≤ 2.…”
Section: Introductionsupporting
confidence: 80%
“…In the next theorems, we state the D ν -analogue results obtained in [7,8,14], and we generalize the results stated in [2,4,12,15] for ν = ω, and in [3,16] for ν = q, respectively. Moreover, we give a complete description of the D ν -semiclassical discrete orthogonal polynomials in the framework of (M, N )-D ν -coherence of order (m, k).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation